VD_FINDINFO Pron / 2013 / 87 vom 5. April 2013 - VD Tribunal cantonal (2013)
AVOCAT D'OFFICE, HONORAIRES, FRAIS JUDICIAIRES, RADIATION DU RÔLE, TRANSACTIONACCORD | 122 al. 1 let. a CPC (CH), 122 al. 1 let. b CPC (CH), 123 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 65 al. 2 TFJC (2010), 67 al. 2 TFJC (2010)